SELLER’S LIABILITY FOR CONFORMITY OF THE GOODS WITH PUBLIC LAW STANDARDS – FROZEN PORK CASE - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
When the goods are exported from one country to another an importantant question arises – do the goods have to comply with the public law requirements of the seller’s country, buyer’s country or even with the rules in effect in some third country. The question is of high importance because the public law requirements, including standards established by environmental law, can have decisive impact on the possibility to use the goods. In order to avoid potential disputes parties should explicitly or implicitly stipulate the qualities of the goods and applicable public law standards. In case law, there are no uniform standards for determination and application of criteria for assesment whether the goods are in conformity with public law requirements. The best solution is to follow the rules established in Mussels case and to consider every case separately. Finally, according to our opinion, fitness for the purpose for which the goods would ordinarily be used does not imply the obligation of the seller to deliver the goods conforming to the public law standards of the import country, unless he knew or ought to have known of such standards. On the other hand, legal standards in effect in buyer’s place or in the place of destination will be relevant when requirements for application of the Art. 35(2)(b) are fulfilled i.e. when particular purpose was expressly or impliedly made known to the seller and when the buyer relied on the seller’s skill and judgement.